Cold Denaturation of Proteins in the Absence of Solvent: Implications for Protein Storage. (21st April 2022) - Norgate, Emma L.; Upton, Rosie; Hansen, Kjetil; Bellina, Bruno; Brookes, C.; Politis, Argyris; Barran, Perdita E.
Abstract: The effect of temperature on the stability of proteins is well explored above 298 K, but harder to track experimentally below 273 K. Variable‐temperature ion mobility mass spectrometry (VT IM‐MS) allows us to measure the structure of molecules at sub‐ambient temperatures. Here we monitor conformational changes that occur to two isotypes of monoclonal antibodies (mAbs) on cooling by measuring their collision cross sections (CCS) at discrete drift gas temperatures from 295 to 160 K. The CCS at 250 K is larger than predicted from collisional theory and experimental data at 295 K. This restructure is attributed to change in the strength of stabilizing intermolecular interactions. Below 250 K the CCS of the mAbs increases in line with prediction implying no rearrangement. Comparing data from isotypes suggest disulfide bridging influences thermal structural rearrangement. These findings indicate that in vacuo deep‐freezing minimizes denaturation and maintains the native fold and VT IM‐MS measurements at sub ambient temperatures provide new insights to the phenomenon of cold denaturation. Abstract : Don't put your protein in the −20 °C freezer: a well‐known fact for biochemists and here it is demonstrated why this is right even in a vacuum. Variable‐temperature ion mobility allows measurement of the structure of isolated proteins at sub‐ambient temperatures. For three isotypes of monoclonal antibody, it is found that there is substantial structural rearrangement at 250 K (−20 °C), indicating a cold denaturation transition. At deep‐freezing temperatures (−80 °C) the structure is unaffected.